Screening de leveduras em fezes de aves em áreas públicas no município de Sinop - MT - Souza, Laryssa de Bryto (2023)
One health is a concept that encompasses the interdependence between human health, animal health and ecosystems. Yeasts can cause opportunistic mycoses in humans and animals, and are often found in bird droppings. Birds, especially urban pigeons, are highly capable of harboring microorganisms such as Candida sp., Pichia sp., Rhodotorula sp. and Trichosporon sp., and because they circulate in various environments, there is a possibility of transmission to humans, which can lead to environmental contamination and infections. Identifying the presence of yeasts with pathogenic potential in samples of pigeon droppings collected in public areas in the north of Mato Grosso is important because these are factors that can influence the health of the population. Samples were collected from places of leisure (gyms and squares) and basic needs (Basic Health Unit, supermarket) with daily circulation of people in the city of Sinop and transported in air-conditioned boxes to the UFMT LAMP for processing and carrying out classic macro and microscopic analyses such as research into capsulated yeasts of the Cryptococcus sp genus using India ink and culture on CHROMagar Candida for presumptive identification of yeasts of the Candida genus, as well as germ tube tests, methylene blue and microcultivation on Fubá Tween 80 agar. A total of 86 samples were collected from 9 locations in Sinop. After testing, C. tropicalis was identified in 55 samples (63.95%), followed by C. krusei 9 (10.46%), Rhodotorula spp 7 (8.14%), T. asahii 3 (3.49%), P. kudriavzevii 3 (3.49%), N. glabrata 2 (2.33%), D. rugosa 2 (2.33%), other species 2 (2.33%), C. lusitaniae 1 (1.16%), C. africana 1 (1.16%) and A. loubieri 1 (1.16%). The identification showed a high presence of pathogenic yeasts isolated in pigeon droppings in different public environments in Sinop, causing a risk of infection in humans and animals passing through these places. Noteworthy was the identification, for the first time in Brazil, of the yeast C. africana present in bird droppings.